2018
DOI: 10.1093/cid/ciy452
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Opioid Therapy in People Living With Human Immunodeficiency Virus: Patients’ Perspectives on Risks, Monitoring, and Guidelines

Abstract: Among PLHIV on COT, opioid misuse (COMM™) and awareness of the addictive potential of COT are common yet COT monitoring practices were not concordant with guidelines. Patients who received monitoring practices reported high satisfaction. When effective implementation of guidelines for care of PLHIV on COT occurs, patient attitudes suggest high acceptance of such practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Furthermore, the intended purposes of these instruments are fairly transparent, and higher risk patients responding in a manner suggesting lower-than-actual risk has been documented 28. Although early studies of the COMM15,16,29 substantiated the validity of the measure through significant relationships with UDT results, both the current study and another 2019 investigation30 of HIV-positive patients taking opioids did not find a significant relationship. These more recent findings may be reflective of the changes in opioid prescribing and monitoring occurring over the past few years.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, the intended purposes of these instruments are fairly transparent, and higher risk patients responding in a manner suggesting lower-than-actual risk has been documented 28. Although early studies of the COMM15,16,29 substantiated the validity of the measure through significant relationships with UDT results, both the current study and another 2019 investigation30 of HIV-positive patients taking opioids did not find a significant relationship. These more recent findings may be reflective of the changes in opioid prescribing and monitoring occurring over the past few years.…”
Section: Discussioncontrasting
confidence: 50%
“…That social awareness may, ironically, encourage greater use of LTOT out of an interest in reducing racial disparities and/or encouraging economically vulnerable patients to stay in care (Knight et al 2017). Further, the physicians in this study served as primary care providers for patients living with HIV-a disease with its own robust legacies of racial disparity (Parker et al 2019), and which presents its own imperatives to keep patients in care (Colasanti et al 2018). On the one hand, Dr. Harris's perspective on LTOT is shaped by a clear awareness of the role his safety net hospital plays for his patients.…”
Section: Scalar Situationsmentioning
confidence: 95%
“…11 Despite these concerns, until recently, there have been insufficient efforts to promote more judicious opioid prescribing for chronic pain and attention to addressing unsafe patterns of opioid use in HIV clinical settings. [12][13][14][15][16][17][18][19][20] Prior studies of opioid use among PWH lack comprehensive assessment of self-reported opioid use regardless of source of opioid and reason for use; they generally focused on prescribed opioid use (i.e., based on pharmacy data), 6,8,21 self-reported extramedical opioid use , [22][23][24][25][26] or the relationship between prescribed opioids and extra-medical opioid use. 9,27 Moreover, these prior studies did not have self-reported data linked with pharmacy data to robustly evaluate the impact of prescribed opioids or psychoactive medications for common comorbidities associated with opioid use (i.e., prescribed benzodiazepines, gabapentinoids, and antidepressants).…”
Section: Introductionmentioning
confidence: 99%